External collaboration & CPFR - McCarthy Byrne, Teresa M. (Henry Stewart Talks, 2023)
Silo forecasting, Production, Marketing & sales, Procurement, Finance, Logistics, R&D, Time horizon, Trading partners, Strategy and planning, Demand and supply management, Execution, Analysis